(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2020)
The study aims at detecting agricultural landuse change and its prediction by using the Markov model in Tarakanda Upazila of Mymensingh District during 1989-2018 which is one of the most fish farming dominated areas of Bangladesh. Therefore, agricultural landuse is converted to the fish farming sector as well as other sectors. In such a situation the study intends at identifying agricultural landuse shifting to various sectors from 1989 to 2018 and predicting it for the year of 2026 as a future vector of the Markov model. The study was conducted using multispectral data from Landsat imageries. The imageries for the years of 1989, 2000, 2010 and 2018 were collected from Landsat 4-5TM and Landsat 8 OLI-TRIS. Maximum likelihood classification and supervised classification were applied to detect landcovers of the study area. The study showed that in 1989, there was 58.55% of agricultural land, but it stood at 46.65% in 2018. About 11.9% of agricultural land has also decreased during 1989-2018. Therefore, yearly about 0.4% of agricultural land has decreased from 1989 to 2018. The predicted data shows that about 2.96% of agricultural land will be decreased from 2018-2026, hence, about 0.37% of agricultural land will be decreased in the near future in the study area. As a fish farming dominated area, the water body of the Tarakanda Upazila has increased by about 0.18% per year, similarly, other sectors have decreased at 0.21 percent per year. Therefore the landuse change dynamics should be considered seriously for future planning. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(1), 2019, P 19-31